Liberalism in Dark Times : The Liberal Ethos in the Twentieth Century - Cherniss, Joshua L. (Joshua Laurence), 1979- (Book collections on Project MUSE., 2021)
"A timely defense of liberalism that draws vital lessons from its greatest midcentury proponents. Today, liberalism faces threats from across the political spectrum. While right-wing populists and leftist purists righteously violate liberal norms, theorists of liberalism seem to have little to say. In Liberalism in Dark Times, Joshua Cherniss issues a rousing defense of the liberal tradition, drawing on a neglected strand of liberal thought. Assaults on liberalism-a political order characterized by limits on political power and respect for individual rights-are nothing new. Early in the twentieth century, democracy was under attack around the world, with one country after another succumbing to dictatorship. While many intellectuals dismissed liberalism as outdated, unrealistic, or unworthy, a handful of writers defended and reinvigorated the liberal ideal, including Max Weber, Raymond Aron, Albert Camus, Reinhold Niebuhr, and Isaiah Berlin-each of whom is given a compelling new assessment here. Building on the work of these thinkers, Cherniss urges us to imagine liberalism not as a set of policies but as a temperament or disposition-one marked by openness to complexity, willingness to acknowledge uncertainty, tolerance for difference, and resistance to ruthlessness. In the face of rising political fanaticism, he persuasively argues for the continuing importance of this liberal ethos"--